PEMBERDAYAAN MASYARAKAT MELALUI MANAJEMEN BISNIS SYARIAH PENJUALAN PRODUK KULIT BUAH MANGGIS PADAMASA PANDEMI COVID-19 DI KAMPUNG CENGAL, DESA KARACAK, KECAMATAN LEUWILIANG, KABUPATEN BOGOR - Ujang Buchori Muslim; Ermi Suryani; Sindiawati Wiguna (SAHID EMPOWERMENT JOURNAL, 2022)
Community empowerment is very important in improving a business or business to reduce the economic impact due to the Covid-19 pandemic and improve the welfare of the community. Community Empowerment is carried out in community service activities in Cengal Village, Karacak Village, Leuwiliang District, Bogor Regency. This community service by counseling entrepreneurial sharia business management in developing sales of mangosteen fruit products, helps create marketplace accounts such as shoppee. With this, it will expand the marketing of mangosteen peel products and help market online through social media. The people of Cengal Village have mangosteen rind products such as brewed tea, tea bags, syrup, and mangosteen rind juice drinks. The community is helped by this community service activity.